PROFIL PEMECAHAN MASALAH BARISAN DAN DERET ARITMETIKA SISWA CLIMBER DI SEKOLAH MENENGAH PERTAMA - Eko Sugandi (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2018)
The development of the world of education in Indonesia can not be separated from the influence of globalization, science and technology are always growing rapidly give a comprehensive impact on all aspects of human life, including the sector of education. Resilient and competitive human resources are needed to meet these challenges. Thus, the need to know about Adversity Quotient of a person to know how far a person can survive and overcome the difficulty. Mathematics which is a universal science underlies the development of modern technology and has an important role in various disciplines. The development of problem-solving abilities is also one of the most important aspects in the objectives of mathematics learning, especially on sequence materials and arithmetic series. Arithmetic sequences and series became a very important mathematical concept because of its wide application, so widely used in daily life. So this qualitative research is done with the aim to describe the process of solving the problem of rows and arithmetic series of junior high school students based on Adversity Quotient climber category. Technique of data collection is done by giving of Problem Solving Task (TPM) sequence and arithmetic series and job-based interview. Based on the analysis of research data that has been done, it is concluded that climber students in understanding the problem trend to read the problem twice. In plotting problem solving, climber students have an alternative solution to solve a given problem. At the implementation stage, climber students solve existing problems based on the most appropriate appropriate problem-solving plan and clearly disclose the truth information from the solution of the problem that has been done. The process of re-examining the problem solving, it is clear that the climber's students are re-checking and also trying to find alternative ways to solve the problem by first making an illustration of the drawing before doing the calculation process. Key Word: Problem Solving, Arithmetic Sequences and Series, Climber